(x-4)+72=90

Simple and best practice solution for (x-4)+72=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-4)+72=90 equation:


Simplifying
(x + -4) + 72 = 90

Reorder the terms:
(-4 + x) + 72 = 90

Remove parenthesis around (-4 + x)
-4 + x + 72 = 90

Reorder the terms:
-4 + 72 + x = 90

Combine like terms: -4 + 72 = 68
68 + x = 90

Solving
68 + x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-68' to each side of the equation.
68 + -68 + x = 90 + -68

Combine like terms: 68 + -68 = 0
0 + x = 90 + -68
x = 90 + -68

Combine like terms: 90 + -68 = 22
x = 22

Simplifying
x = 22

See similar equations:

| 4x^2+29=-28x | | 2x-1=7x+3 | | (2x+17)=90 | | 5y-12-y=0 | | -39-7n=-5+2(-8n-8) | | x-(-14)=-39 | | (x-5)+29=90 | | (8a^-9)^2/3 | | 12=1.5timesp | | -2(t-4)-5= | | (2x+5y)+(x+y)=4+1 | | x^3-9x^2+24x-15=0 | | pq+5q+2p+10= | | x-(-53)=30 | | -3(17q)= | | 912*13/81 | | (x+7)+43=90 | | x^2+20=-12 | | -14x-20=12x+7 | | 3n+4(-4n+1)=2n+4 | | 2m^2+2m-18=0 | | 4x^2+57=28 | | 3(17q)= | | 36m*36m+20m-16= | | (-4)+x=69 | | 9(x+8)-6(x-3)+14=5(x-3)+11 | | -3.5n=2.51 | | B^2+8b=64 | | 3x^2+60=24x | | .80x+x=162 | | g(x)=-x^3+2x^2+11x-12 | | 3.2+0.3x=0.2+1.14 |

Equations solver categories